Gamma delta T-cell reconstitution after allogeneic HCT: A platform for cell therapy - Gaballa, Ahmed; Arruda, Lucas C. M.; Uhlin, Michael (Frontiers in Immunology, 2022)
Allogeneic Hematopoietic stem cell transplantation (allo-HCT) is a curative platform for several hematological diseases. Despite its therapeutic benefits, the profound immunodeficiency associated with the transplant procedure remains a major challenge that renders patients vulnerable to several complications. Today, It is well established that a rapid and efficient immune reconstitution, particularly of the T cell compartment is pivotal to both a short-term and a long-term favorable outcome. T cells expressing a TCR heterodimer comprised of gamma (γ) and delta (δ) chains have received particular attention in allo-HCT setting, as a large body of evidence has indicated that γδ T cells can exert favorable potent anti-tumor effects without inducing severe graft versus host disease (GVHD). However, despite their potential role in allo-HCT, studies investigating their detailed reconstitution in patients after allo-HCT are scarce. In this review we aim to shed lights on the current literature and understanding of γδ T cell reconstitution kinetics as well as the different transplant-related factors that may influence γδ reconstitution in allo-HCT. Furthermore, we will present data from available reports supporting a role of γδ cells and their subsets in patient outcome. Finally, we discuss the current and future strategies to develop γδ cell-based therapies to exploit the full immunotherapeutic potential of γδ cells in HCT setting.